IMPLEMENTASI PERKEMBANGAN NILAI AGAMA DAN MORAL ANAK USIA 5-6 TAHUN PADA KELAS B DI TKIT YA BUNAYYA TAHUN 2021-2022 - Nursila; Novi Cahya Dewi; Hadisa Putri (Samawa (Sakinah, Mawaddah Warahmah), 2024)
This research is motivated by indications that TKIT Ya Bunayya can be said to be unique because apart from providing learning like in general, this institution also emphasizes Islamic values such as memorizing short surahs, iqro', asmaul husna, names of surahs, hadith. Every day, practice the dhuha prayer and get used to the daily prayers. However, during the Duha prayer in class B, some children were still not able to be orderly and orderly, some children were still joking around with their friends, there were also those who were still playing alone when doing prayer movements, some children were still not able to perform ablution properly. And correct and still need guidance and support from the teacher. This research has three research objectives, including the following: First, to find out the role of teachers in developing the religious and moral values of children aged 5-6 years through the method of getting used to the dhuha prayer in class B at TKIT Ya Bunayya in 2021-2022. Second, to find out the implementation of the development of religious and moral values in children aged 5-6 years through the method of getting used to the Dhuha prayer in class B at TKIT Ya Bunayya in 2021-2022. Third, to find out what factors influence the development of religious and moral values in children aged 5-6 years through the method of getting used to the Dhuha prayer in class B at TKIT Ya Bunayya in 2021-2022. This research uses a qualitative approach while this type of research is phenomenological research. There are three types of data collection techniques in this research, namely: Interview, Observation and Documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data display, drawing conclusions and verification. Then the data validity checking techniques used are triangulation (source triangulation) and member check. The results of the research are: First, the role of teachers in developing the religious and moral values of children aged 5-6 years through the method of getting used to the dhuha prayer in class B at TKIT Ya Bunayya in 2021-2022 is the teacher as a guide, planner, teacher, class manager, motivator, innovator, facilitator, and evaluator in learning. Second, the implementation of the development of religious and moral values for children aged 5-6 years through the method of getting used to the Dhuha prayer in class B at TKIT Ya Bunayya in 2021-2022 consists of several things, namely, learning planning, learning implementation and learning evaluation. Third, the factors that influence the development of religious and moral values in children aged 5-6 years through the method of getting used to the Dhuha prayer in class B at TKIT Ya Bunayya in 2021-2022, namely, consist of supporting factors and inhibiting factors.